2016
DOI: 10.1002/jmr.2558
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations on the conformational transitions from the GA98 (GA88) to GB98 (GB88) proteins

Abstract: We performed conventional and targeted molecular dynamics simulations to address the dynamic transition mechanisms of the conformational transitions from the G 98 protein with only 1 mutation of Leu45Tyr to G 98 and from the G 88 protein with 7 mutations of Gly24Ala, Ile25Thr, Ile30Phe, Ile33Tyr, Leu45Tyr, Ile49Thr, and Leu50Lys to G 88. The results show that the conformational transition mechanism from the mutated 3α G 98 (G 88) state to the α+4β G 98 (G 88) state via several intermediate conformations involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Also, the refold from 3α to 4β + α upon the mutation L20A in the sequence I25, F30, and Y45 is in agreement with our simulation results (case 14) although the effect is rather weak. To shed further light on the role of residue 45, the folding process 110,111 and the folding kinetics may have to be considered to (in)validate a pure thermodynamic analysis as carried out here. Haloalkane Dehalogenase DhaA.…”
mentioning
confidence: 99%
“…Also, the refold from 3α to 4β + α upon the mutation L20A in the sequence I25, F30, and Y45 is in agreement with our simulation results (case 14) although the effect is rather weak. To shed further light on the role of residue 45, the folding process 110,111 and the folding kinetics may have to be considered to (in)validate a pure thermodynamic analysis as carried out here. Haloalkane Dehalogenase DhaA.…”
mentioning
confidence: 99%
“…Due to the high amount of interest in the protein quality of maize, a close relative of sorghum, the sorghum syntenic orthologues of maize were extracted and compared to three studies on the maize kernel. The first, Wang et al (2016), is a proteomic analysis of intact protein bodies from maize endosperm (Wang et al, 2016). This study identified proteins that make up the composition of kernel protein bodies in maize.…”
Section: Deletions In Alpha-kafirin Genes Caused Alterations In Chrom...mentioning
confidence: 99%
“…This gene corresponds to a subtilisin protease. The syntenic orthologue was found to also be upregulated in o2 maize endosperms (Zhan et al, 2018), a component of maize protein bodies (Wang et al, 2016), as well associated with methionine to lysine ratio via GWAS (Shrestha et al, 2022). Interestingly, a second subtilisin protease was also upregulated in edited lines (SbiRTX430.06G174000).…”
Section: Deletions In Alpha-kafirin Genes Caused Alterations In Chrom...mentioning
confidence: 99%
“…The molecular mechanics Poisson-Boltzmann surface area (MM-PBSA) method was used to perform the binding free energy analysis in AMBER16 package [55,56]. The binding free energy (ΔG binding ) was calculated based on the followed equation:…”
Section: Binding Free Energy Analysismentioning
confidence: 99%